Python from scratch : LiveLessons (LiveLessons (Indianapolis, Ind.), 2017)
"Python from Scratch LiveLessons is a gentler, more entertaining, and more practical starting point to learning the Python programming language. Unlike the typical approach to teaching a programming language that covers each feature section by section, this course is structured more like a cooking class. You can follow along and execute all the code being demonstrated in an interactive notebook as you watch the video, much the same way you would watch a cooking video in your kitchen."--Resource description page.